The trouble with nouns and verbs in Greek fluent aphasia - Kambanaros, Maria (My University, 2008)
In the past verb retrieval problems were associated primarily with agrammatism and noun retrieval difficulties with fluent aphasia. With regards to fluent aphasia, so far in the literature, three distinct patterns of verb/noun dissociations have been described for individuals with fluent anomic aphasia in languages with different underlying forms; better verb retrieval, poorer verb retrieval and equal retrieval difficulties for verbs and nouns. Verbs and nouns in Greek are considered of similar morphological complexity thus it was predicted that anomic aphasic individuals would suffer from a non-dissociated impairment of verbs and nouns. Problems with verbs and/or nouns may arise at any stage in the process of lexical retrieval, i.e. lexical-semantic, lemma, lexeme or articulation. The aim of this research was to investigate verb and noun retrieval using a picture-naming task to explore any possible selective noun and/or verb comprehension or retrieval deficits in Greek individuals with anomic aphasia. The results revealed a significant verb/noun dichotomy with verbs significantly more difficult to retrieve than nouns. These findings lend support for the growing body of evidence showing a specific verb impairment in fluent anomic individuals as well as Broca's patients. Given the prevailing view, that anomic patients experience difficulty retrieving the morpho-phonological form of the target word, the results show that specific information of the grammatical category is also important during word form retrieval. LEARNER OUTCOMES: The reader will become familiar with (i) studies investigating grammatical word class breakdown in individuals with aphasia who speak different languages, (ii) the application of the serial model to word production breakdown in aphasia and (iii) the characteristics of verbs and nouns in Greek. It will be concluded that successful verb retrieval for fluent aphasic individuals who speak Greek is dependant on the retrieval of the morpho-phonological information of the target verb.
Keywords: Aphasia; Agrammatic aphasia; Speech disorder